Security Control Systems Decelopment Laboratory In Space Hardware-Based Microcontroller Atmega 16 - Asriani , Irma; Sari, Eka Purnama; Asnawati , Asnawati (Jurnal Komputer Indonesia, 2022)
Development of control systems security lab space is a tool that can help secure laboratory space equipped with automatic electric locks and alarms. This security system uses a programming language Bascom Avr programming language more easily understood and to understand than other BASIC language. The results of these research activities is the control system security at the lab space in order to create a sense of security for faculty and students as he left the lab space, because the automatic lock is mounted on the main door and cabinet and is equipped with an alarm.